Managing Green Business Model Transformations - Sommer, Axel.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Environmental sustainability creates both tremendous business opportunities and formidable threats to established companies across virtually all industry sectors. Yet many companies tackle the issue in a superficial or passive way through increased environmental reporting, the use of “greenspeak” in their corporate communication activities or isolated efforts to create green products or reduce pollution. In contrast, there are a small but increasing number of firms that employ a holistic approach to sustainability and consider fundamental changes to their existing business models. By ignoring the opportunities of Green Business Model Transformations, companies exclude themselves from a large variety of potential means to create economic value. In addition to ordinary product and process innovations, they can change “the rules of the game” within an industry towards environmental sustainability. This can facilitate the commercialisation of new green products that would not be competitive otherwise targeting new customer segments with previously unmet needs improved economics of value creation by developing a green architecture of the firm and its business network Green Business Model Transformations, however, are challenging ventures in many respects: Firstly, it is difficult to develop and accurately assess the prospects of new, green business models due to uncertainties and inherent complex systemic characteristics. It can therefore be very challenging for individual managers of established companies to question the status quo and seize new, green opportunities. The implementation of Green Business Model Transformations therefore requires strong change capabilities: The stakes are high, many otherwise disconnected parts of the organisation are involved, and the subject matter is complex in nature. As a result, there is a great need for guidance in management practice that current research does not address. This publication aims to fill this gap with a general approach to Managing Green Business Model Transformations by defining a process to evaluate green business models and providing a methodology for their realisation.
Part I – Introduction -- The Emergence of Green Business Models -- Purpose of this Work and Research Approach -- Part II – Theoretical Foundation of Green Business Model Transformations -- Environmental Sustainability in Business -- The Business Model Concept as a Unit of Analysis for Management Science -- Towards a Taxonomy of Green Business Models.-  Organisations, Change, and Innovation -- Part III – Towards a Practical Management Approach -- A Survey on Green Business Model Transformations -- Managerial Implications of Survey Results -- Managing Green Business Model Transformations – A Framework for Management Practice -- Part IV – Conclusion and Outlook -- Conclusion and Outlook.
Keywords: Engineering economics; Engineering economy; Management; Industrial management; Sustainable development; Organization; Planning; Engineering Economics, Organization, Logistics, Marketing; Innovation/Technology Management; Sustainable Development; Organization; Management